Liquid crystal alignment agent, liquid crystal alignment film, and liquid crystal display element
Patent Information
- Application Number
- CN202311084305.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-03-19
- Filing Date
- 2019-03-18
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2039-03-18
AI Technical Summary
但是,随着液晶表示元件的高性能化,液晶取向膜所要求的特性越来越严格,这些现有技术难以充分满足所有所要求的特性
[0025]根据本发明的液晶取向剂,能够提供电压保持率优异、蓄积电荷的缓和快、液晶取向性、透明性良好的液晶取向膜、及显示特性优异的液晶表示元件。
Smart Images

Figure CN117148630B_ABST
Abstract
Description
[0001] This application is a divisional application of Chinese patent application No. 201980020161.8, filed on March 18, 2019, entitled "Liquid Crystal Alignment Agent, Liquid Crystal Alignment Film and Liquid Crystal Display Element". Technical Field
[0002] This invention relates to novel liquid crystal alignment agents, liquid crystal alignment films, and liquid crystal display elements using the same. Background Technology
[0003] Liquid crystal display elements (LCDs) are widely used as display components in computers, mobile phones, smartphones, televisions, and other devices. An LCD typically includes: a liquid crystal layer sandwiched between a substrate and a color filter substrate; pixel electrodes and a common electrode that apply an electric field to the liquid crystal layer; an alignment film that controls the alignment of the liquid crystal molecules in the liquid crystal layer; and thin-film transistors (TFTs) that switch the electrical signals supplied to the pixel electrodes. Known driving methods for liquid crystal molecules include vertical electric field methods such as TN and VA, and lateral electric field methods such as IPS and FFS. Compared to existing vertical electric field methods that apply voltage to electrodes formed on both upper and lower substrates to drive the liquid crystal, the lateral electric field method, which forms an electrode on only one side of the substrate and applies an electric field in a direction parallel to the substrate, is well-known for its wider viewing angle and ability to achieve high-quality displays.
[0004] While liquid crystal cells using a lateral electric field method offer excellent field-of-view characteristics, they have fewer electrode portions within the substrate. Therefore, when the voltage retention rate is low, insufficient voltage is applied to the liquid crystal, leading to reduced display contrast. Furthermore, low liquid crystal alignment stability means that the liquid crystal cannot return to its initial state after prolonged driving, resulting in reduced contrast and ghosting. Thus, liquid crystal alignment stability is crucial. Moreover, static electricity easily accumulates within the liquid crystal cell. The application of asymmetrical positive and negative voltages generated during driving also causes charge accumulation within the cell. This accumulated charge affects the display in the form of misaligned liquid crystals and ghosting, significantly degrading the display quality of the liquid crystal element.
[0005] As a liquid crystal alignment agent that exhibits excellent voltage retention and reduces charge accumulation when used in liquid crystal display elements with such a lateral electric field, Patent Document 1 discloses a liquid crystal alignment agent containing a specific diamine and an aliphatic tetracarboxylic acid derivative. Furthermore, as a method to shorten the time until afterimage disappearance, methods have been proposed using alignment films with low volume resistivity, such as those in Patent Document 2, and alignment films with volume resistivity that is not easily affected by the backlight of the liquid crystal display element, such as those in Patent Document 3. However, with the increasing performance of liquid crystal display elements, the characteristics required for liquid crystal alignment films are becoming increasingly stringent, and these existing technologies are insufficient to fully meet all the required characteristics.
[0006] Existing technical documents
[0007] Patent documents
[0008] Patent Document 1: International Publication (WO) 2004 / 021076 Booklet
[0009] Patent Document 2: International Publication (WO) 2004 / 053583 (Booklet)
[0010] Patent Document 3: International Publication (WO) 2013 / 008822 (booklet) Summary of the Invention
[0011] The problem the invention aims to solve
[0012] The objective of this invention is to provide a liquid crystal alignment agent, a liquid crystal alignment film, and a liquid crystal display element that can produce a liquid crystal alignment film with excellent voltage retention, rapid charge accumulation, good liquid crystal alignment, and good transparency.
[0013] Solution for solving the problem
[0014] In order to solve the above-mentioned problems, the inventors conducted in-depth research and as a result completed this invention.
[0015] The present invention is a liquid crystal alignment agent, characterized in that it contains the following components (A), (B), and an organic solvent.
[0016] (A) Composition: Polymer
[0017] (B) Components: Compounds represented by the following formula (1)
[0018]
[0019] (where Q is in the formula) 1 and Q 2 Q is selected from one of the following (Q1-1) and a single bond. 1 and Q 2 At least one of them is (Q1-1),
[0020]
[0021] q1 and q2 are each independently 0 or 1.
[0022] R 1 It can be a hydrogen atom or a monovalent organic group.
[0023] R 2 and R 3 R can be any one of the groups having an epoxy site and a hydrogen atom, respectively.2 and R 3 At least one of them is a group having an epoxy site.
[0024] The effects of the invention
[0025] The liquid crystal alignment agent according to the present invention can provide a liquid crystal alignment film with excellent voltage retention, rapid charge accumulation, good liquid crystal alignment and transparency, and a liquid crystal display element with excellent display characteristics.
[0026] The reasons why the present invention can solve the above-mentioned problems have not yet been determined, but are generally believed to be as follows. The structure of the compound represented by the above formula (1) contained in the liquid crystal alignment agent of the present invention has a conjugated structure. As a result, for example, it can promote the movement of charges in the liquid crystal alignment film and promote the mitigation of accumulated charges. Detailed Implementation
[0027] <(A)Component>
[0028] The liquid crystal alignment agent of the present invention contains component (A), which is at least one polymer selected from the group consisting of a polyimide precursor, an imidized polymer of the polyimide precursor, and a photosensitive side-chain acrylic polymer that exhibits liquid crystal properties within a specified temperature range.
[0029] <Polyimide precursor>
[0030] The polyimide precursor of component (A) has a structural unit represented by the following formula (A1).
[0031]
[0032] In formula (A1), X1 is a tetravalent organic group and Y1 is a divalent organic group.
[0033] R1 is a hydrogen atom or an alkyl group having 1 to 5 carbon atoms, and A1 and A2 are each independently a hydrogen atom, an alkyl group having 1 to 10 carbon atoms with a substituent, an alkenyl group having 2 to 10 carbon atoms with a substituent, or an alkynyl group having 2 to 10 carbon atoms with a substituent, respectively.
[0034] Specific examples of alkyl groups in R1 include methyl, ethyl, propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, and n-pentyl. From the viewpoint of ease of imidization upon heating, R1 is preferably a hydrogen atom or a methyl group.
[0035] X1 is a tetravalent organic group derived from a tetracarboxylic acid derivative, and its structure is not particularly limited. In polyimide precursors, two or more types of X1 can coexist.
[0036] As a specific example of X1, the structures of the following formulas (X-1) to (X-44) can be listed.
[0037]
[0038]
[0039] In the above formula (X-1), R8~R 11 Each of the following is independently a hydrogen atom, a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkenyl group having 2 to 6 carbon atoms, an alkynyl group having 2 to 6 carbon atoms, or a phenyl group. R8 to R 11 When the structure is large, it may reduce the orientation of the liquid crystal. Therefore, hydrogen atoms, methyl groups or ethyl groups are preferred, and hydrogen atoms or methyl groups are particularly preferred.
[0040] From the perspective of the availability of monomers, X1 is preferably selected from the structures of formulas (X-1) to (X-14).
[0041] The preferred proportion of the structure selected from the above formulas (X-1) to (X-14) is 20 mol% or more of the total X1, more preferably 60 mol% or more, and even more preferably 80 mol% or more.
[0042] A1 and A2 are each independently a hydrogen atom, an alkyl group having 1 to 10 carbon atoms with a substituent, an alkenyl group having 2 to 10 carbon atoms with a substituent, or an alkynyl group having 2 to 10 carbon atoms with a substituent, respectively.
[0043] Specific examples of the aforementioned alkyl groups include methyl, ethyl, propyl, butyl, tert-butyl, hexyl, octyl, decyl, cyclopentyl, cyclohexyl, and dicyclohexyl.
[0044] As an alkenyl group, examples include those obtained by replacing one or more CH2-CH2 structures present in the aforementioned alkyl groups with CH=CH structures. Specifically, examples include vinyl, allyl, 1-propenyl, isopropenyl, 2-butenyl, 1,3-butadienyl, 2-pentenyl, 2-hexenyl, cyclopropenyl, cyclopentenyl, cyclohexenyl, etc.
[0045] As an alkynyl group, examples include groups obtained by replacing one or more CH2-CH2 structures present in the aforementioned alkyl groups with C≡C structures. Specifically, examples include ethynyl, 1-propynyl, and 2-propynyl.
[0046] The aforementioned alkyl, alkenyl, and alkynyl groups can have substituents, or the substituents can form ring structures. It should be noted that the formation of ring structures by substituents refers to the formation of ring structures by the substituents bonding with each other or with a portion of the parent skeleton.
[0047] Examples of the substituents mentioned above include halogen groups, hydroxyl groups, thiols, nitro groups, aryl groups, organooxy groups, organosulfur groups, organosilicon groups, acyl groups, ester groups, thioester groups, phosphate ester groups, amide groups, alkyl groups, alkenyl groups, and alkynyl groups.
[0048] Halogen groups that are substituents can include fluorine atoms, chlorine atoms, bromine atoms, or iodine atoms.
[0049] Aryl groups that are not substituents include phenyl groups. These aryl groups can then be substituted by the other substituents mentioned above.
[0050] The substituent organic oxygen group can be represented by the structure denoted by -OR. This R can be the same or different, and examples include the aforementioned alkyl, alkenyl, alkynyl, aryl, etc. These R groups can then be substituted by the aforementioned substituents. Specific examples of organic oxygen groups include methoxy, ethoxy, propoxy, butoxy, pentoxy, hexoxy, heptoxy, octoxy, etc.
[0051] The organothio group that is a substituent can be represented by the structure denoted by -SR. Examples of R include the aforementioned alkyl, alkenyl, alkynyl, aryl, etc. These Rs can be further substituted by the aforementioned substituents. Specific examples of organothio groups include methylthio, ethylthio, propylthio, butylthio, pentylthio, hexylthio, heptylthio, octylthio, etc.
[0052] Substituent organosilanes can exhibit a structure represented by -Si-(R)3. The R group can be the same or different, and examples include the aforementioned alkyl, alkenyl, alkynyl, aryl, etc. These R groups can further be substituted by the aforementioned substituents. Specific examples of organosilanes include trimethylsilyl, triethylsilyl, tripropylsilyl, tributylsilyl, tripentylsilyl, trihexylsilyl, pentyldimethylsilyl, hexyldimethylsilyl, etc.
[0053] The acyl group that is a substituent can be represented by a structure of -C(O)-R. Examples of R include the aforementioned alkyl, alkenyl, aryl, etc. These Rs can be further replaced by the aforementioned substituents. Specific examples of acyl groups include formyl, acetyl, propionyl, butyryl, isobutyryl, valeryl, isovaleryl, benzoyl, etc.
[0054] The ester group that is substituent can exhibit a structure represented by -C(O)OR or -OC(O)-R. Examples of R include the aforementioned alkyl, alkenyl, alkynyl, aryl, etc. These Rs can then be substituted by the aforementioned substituents.
[0055] The thioester group that is a substituent can exhibit a structure represented by -C(S)OR or -OC(S)-R. Examples of R include the aforementioned alkyl, alkenyl, alkynyl, aryl, etc. These Rs can then be substituted by the aforementioned substituents.
[0056] The phosphate ester group with substituents can be represented by the structure -OP(O)-(OR)2. This R can be the same or different, and can be exemplified by the aforementioned alkyl, alkenyl, alkynyl, aryl, etc. These R groups can then be substituted by the aforementioned substituents.
[0057] The amide group that is substituent can exhibit structures represented by -C(O)NH2, or -C(O)NHR, -NHC(O)R, -C(O)N(R)2, -NRC(O)R. The R group can be the same or different, and can be exemplified by the aforementioned alkyl, alkenyl, alkynyl, aryl, etc. These R groups can then be substituted by the aforementioned substituents.
[0058] The aryl group that is a substituent can be an example of an aryl group that is identical to the aforementioned aryl group. This aryl group can then be substituted by the aforementioned other substituents.
[0059] The alkyl group that is substituted can be the same as the aforementioned alkyl group. This alkyl group can then be substituted by the other aforementioned substituents.
[0060] The alkenyl group that is a substituent can be the same as the alkenyl group mentioned above. This alkenyl group can then be substituted by the other substituents mentioned above.
[0061] The alkynyl group that is a substituent can be the same as the aforementioned alkynyl group. This alkynyl group can then be substituted by the aforementioned other substituents.
[0062] Typically, when introducing a large structure, the reactivity and liquid crystal orientation of the amino group may be reduced. Therefore, hydrogen atoms or optional alkyl groups with 1 to 5 carbon atoms having substituents are preferred as A1 and A2. Hydrogen atoms, methyl groups, or ethyl groups are particularly preferred.
[0063] Y1 is a divalent organic group derived from a diamine, and its structure is not particularly limited. Specific examples of Y1 can be listed as follows: formulas (Y-1) to (Y-119).
[0064]
[0065]
[0066]
[0067]
[0068]
[0069] In equation (Y-109), m and n are integers from 1 to 11, and m+n is an integer from 2 to 12.
[0070] In equation (Y-114), h is an integer from 1 to 3, and in equations (Y-111) and (Y-117), j is an integer from 0 to 3.
[0071] Y1 is more preferably selected from at least one of the structures represented by the following formulas (5) and (6) from the viewpoint of the liquid crystal alignment property and pretilt angle of the obtained liquid crystal alignment film.
[0072]
[0073] In equation (5), R 12 R is a single bond or a divalent organic group having 1 to 30 carbon atoms. 13 It is a hydrogen atom, a halogen atom, or a monovalent organic group having 1 to 30 carbon atoms, where a is an integer from 1 to 4. When a is 2 or more, R... 12 and R 13 They can be the same or different.
[0074] In equation (6), R 14 For single bonds, -O-, -S-, -NR 15 - amide bond, ester bond, urea bond, or divalent organic group with 1 to 40 carbon atoms, R 15 It can be a hydrogen atom or a methyl group.
[0075] As specific examples of Y1 represented by equations (5) and (6), the following structures in the aforementioned equations (Y-1) to (Y-119) can be listed.
[0076] The Y1 structure with high linearity can improve the alignment of liquid crystal when it is made into a liquid crystal alignment film. Therefore, the preferred formulas are (Y-7), (Y-21), (Y-22), (Y-23), (Y-25), (Y-43), (Y-44), (Y-45), (Y-46), (Y-48), (Y-63), (Y-71), (Y-72), (Y-73), (Y-74), (Y-75), (Y-98), (Y-99), (Y-100), or (Y-118).
[0077] The proportion of the structure of Y1 that can improve the orientation of the liquid crystal is preferably 20 mol% or more of the total Y1, more preferably 60 mol% or more, and even more preferably 80 mol% or more.
[0078] When fabricating a liquid crystal alignment film, if it is desired to increase the pretilt angle of the liquid crystal, Y1 preferably has a structure in which the side chains have long-chain alkyl groups, aromatic rings, aliphatic rings, steroid backbones, or combinations thereof. As such Y1, formulas (Y-76) to (Y-97) are preferred. The proportion of the above-mentioned Y1 structure for increasing the pretilt angle is preferably 1 to 30 mol% of the total Y1, more preferably 1 to 20 mol%.
[0079] Furthermore, when using a polyimide precursor or polyimide with photooriented side chains as the polymer of component (A), it is preferable that the polyimide precursor or polyimide has the following photoreactive side chains.
[0080] -R 6 -R 7 -R 8 -R 9 (c)
[0081] (In equation (c), R) 6 Represents -CH2-, -O-, -COO-, -OCO-, -NHCO-, -CONH-, -NH-, -CH2O-, -N(CH3)-, -CON(CH3)-, or -N(CH3)CO-. R 7 Represents a cyclic, unsubstituted, or fluorine-substituted alkylene group having 1 to 20 carbon atoms (any -CH2- group of the alkylene group can be replaced by -CF2- or -CH=CH-, or by any of the following groups in a non-adjacent manner (as groups, -O-, -COO-, -OCO-, -NHCO-, -CONH-, -NH-, carbocyclic, or heterocyclic). R 8 Represents -CH2-, -O-, -COO-, -OCO-, -NHCO-, -NH-, -N(CH3)-, -CON(CH3)-, -N(CH3)CO-, carbocyclic rings, or heterocyclic rings. R 9 Indicates vinylphenyl, -CR 10 =CH2 group, -CR 10 (OH)-CH3 group, carbocyclic, heterocyclic, or a structure represented by the following formula, R 10 (This represents a hydrogen atom or a methyl group that is optionally substituted with a fluorine atom.)
[0082]
[0083]
[0084] When manufacturing the above-mentioned polyimide precursor, it is relatively simple to obtain the diamine by substituting the side chain represented by the above formula (c).
[0085] Alternatively, polyimide precursors with photo-orientation groups in the main chain can also be used. In this case, it is more convenient to use a diamine with a bond containing photo-orientation groups between amines, as represented by the following formula (2).
[0086]
[0087] In equation (2), X 1 It is a single bond or an alkylene group having 1 to 5 carbon atoms, X 2 For -OCO-CH=CH- or -CH=CH-COO-, X 3 It is a single bond, an alkylene ring with 1 to 10 carbon atoms, or a divalent benzene ring, X 4 For single bonds, -OCO-CH=CH- or -CH=CH-COO-, X 5 It is a single bond or an alkylene group having 1 to 5 carbon atoms. It contains one or more cinnamoyl groups.
[0088] As diamines represented by formula (2), the following formulas (2-a) to (2-d) can be listed.
[0089]
[0090] In the formula, X is a bonding group selected from single bonds or ethers (-O-), esters (-COO- or OCO-), and amides (-CONH- or NHCO-), Y is a single bond or an alkylene group with 1 to 5 carbon atoms, and Z is an alkylene group with 1 to 10 carbon atoms or a phenylene group. There are no particular limitations on the bonding position of the amino group on the benzene ring or the position of the bonding group relative to the central benzene ring.
[0091] Furthermore, as specific examples of diamines represented by formula (2), the following diamines can be listed.
[0092]
[0093]
[0094] For liquid crystal alignment films formed using polyimide precursors such as polyamic acid and polyamic acid esters, polyimides, or polyamides of the present invention, which contain diamines represented by formula (2) above as raw materials, the changes in liquid crystal alignment properties based on AC (alternating current) driving, such as changes in the orientation of the liquid crystal, are reduced. Therefore, the liquid crystal alignment properties of the liquid crystal alignment film in a liquid crystal display element having this liquid crystal alignment film are stable when AC driving is used, and thus it is less likely to produce afterimages caused by AC driving. That is, it achieves a very good effect in exhibiting afterimage characteristics based on AC driving.
[0095] Furthermore, the liquid crystal alignment film formed using the diamine represented by the above formula (2) has excellent liquid crystal alignment properties and can form a liquid crystal alignment film that is substantially free of alignment defects.
[0096] The polyimide precursor used in this invention is obtained by reacting a diamine component with a tetracarboxylic acid derivative, such as polyamic acid and polyamic acid ester.
[0097] <Manufacturing of polyimide precursor (polyamic acid)>
[0098] Polyamic acid, the polyimide precursor used in this invention, is manufactured using the following method. Specifically, it can be synthesized by reacting tetracarboxylic dianhydride and diamine in the presence of an organic solvent at -20 to 150°C, preferably 0 to 50°C, for 30 minutes to 24 hours, preferably 1 to 12 hours.
[0099] The reaction between the diamine and the tetracarboxylic acid components is typically carried out in an organic solvent. There are no particular limitations on the organic solvent used, as long as it dissolves the resulting polyimide precursor. Specific examples of organic solvents used in the reaction are listed below, but the reaction is not limited to these examples. Examples include N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone or γ-butyrolactone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide or 1,3-dimethylimidazolinone.
[0100] In addition, when the polyimide precursor has high solubility, methyl ethyl ketone, cyclohexanone, cyclopentanone, 4-hydroxy-4-methyl-2-pentanone or organic solvents of formulas [D-1] to [D-3] can be used.
[0101]
[0102] In formula [D-1], D 1 In formula [D-2], D represents an alkyl group having 1 to 3 carbon atoms. 2 It represents an alkyl group having 1 to 3 carbon atoms, in the formula [D-3], where D 3 Indicates an alkyl group having 1 to 4 carbon atoms.
[0103] These organic solvents can be used alone or in combination. Furthermore, even solvents that do not dissolve the polyimide precursor can be mixed with the aforementioned solvents to the extent that the generated polyimide precursor will not precipitate. In addition, since water in the organic solvent can hinder the polymerization reaction and thus cause the generated polyimide precursor to hydrolyze, it is preferable to use a dehydrated and dried organic solvent.
[0104] The concentration of the polyamic acid polymer in the reaction system is preferably 1 to 30% by mass, more preferably 5 to 20% by mass, from the perspective of minimizing polymer precipitation and easily obtaining high molecular weight polymers.
[0105] The polyamic acid obtained through the above operation can be recovered by precipitating the polymer by injecting it into a poor solvent while the reaction solution is thoroughly stirred. Alternatively, multiple precipitation processes can be performed, followed by washing with a poor solvent and drying at room temperature or with heat to obtain purified polyamic acid powder. Poor solvents are not particularly limited and examples include water, methanol, ethanol, hexane, butyl cellosolve, acetone, and toluene.
[0106] <Manufacturing of Polyimide Precursors (Polyamates)>
[0107] The polyamide ester used as the polyimide precursor in this invention can be manufactured using the methods shown in (1), (2) or (3) below.
[0108] (1) Cases involving polyamic acid
[0109] Polyamic acid esters can be manufactured by esterifying polyamic acid produced by the above operation. Specifically, they can be manufactured by reacting polyamic acid and an esterifying agent in the presence of an organic solvent at -20 to 150°C, preferably 0 to 50°C, for 30 minutes to 24 hours, preferably 1 to 4 hours.
[0110] As esterifying agents, those that can be easily removed through purification are preferred, including: N,N-dimethylformamide dimethyl acetal, N,N-dimethylformamide diethyl acetal, N,N-dimethylformamide dipropyl acetal, N,N-dimethylformamide dineopentylbutyl acetal, N,N-dimethylformamide ditert-butyl acetal, 1-methyl-3-p-tolyltriazine, 1-ethyl-3-p-tolyltriazine, 1-propyl-3-p-tolyltriazine, 4-(4,6-dimethoxy-1,3,5-triazin-2-yl)-4-methylmorpholinium chloride, etc. The amount of esterifying agent added is preferably 2 to 6 molar equivalents relative to 1 mole of the repeating unit of polyamic acid.
[0111] Examples of organic solvents include N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, or γ-butyrolactone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, or 1,3-dimethylimidazolinone. Furthermore, where the polyimide precursor has high solvent solubility, methyl ethyl ketone, cyclohexanone, cyclopentanone, 4-hydroxy-4-methyl-2-pentanone, or the organic solvents shown in formulas [D-1] to [D-3] can be used.
[0112] These organic solvents can be used alone or in combination. Furthermore, even solvents that do not dissolve the polyimide precursor can be mixed with the aforementioned solvents to the extent that the generated polyimide precursor will not precipitate. In addition, since water in the organic solvent can hinder the polymerization reaction and thus cause the generated polyimide precursor to hydrolyze, it is preferable to use a dehydrated and dried organic solvent.
[0113] The solvents used in the above reactions are preferably N,N-dimethylformamide, N-methyl-2-pyrrolidone, or γ-butyrolactone, considering the solubility of the polymer; one or more of these can be used in combination. The concentration used in manufacturing is preferably 1–30% by mass, more preferably 5–20% by mass, from the viewpoint of minimizing polymer precipitation and readily obtaining high molecular weight polymers.
[0114] (2) The case of preparation by the reaction of tetracarboxylic acid diester dichloride with diamine.
[0115] Polyamates can be manufactured from tetracarboxylate diester dichloride and diamine. Specifically, they can be manufactured by reacting tetracarboxylate diester dichloride and diamine in the presence of a base and an organic solvent at -20 to 150°C, preferably 0 to 50°C, for 30 minutes to 24 hours, preferably 1 to 4 hours.
[0116] As the aforementioned base, pyridine, triethylamine, 4-dimethylaminopyridine, etc., can be used. Pyridine is preferred to ensure a gentle reaction. From the viewpoint of being an amount that is easy to remove and readily yields a high molecular weight product, the amount of base added is preferably 2 to 4 moles relative to the tetracarboxylic acid diester dichloride.
[0117] As the aforementioned organic solvent, considering the solubility of monomers and polymers, N-methyl-2-pyrrolidone or γ-butyrolactone are preferred, and one or more of these can be used.
[0118] The polymer concentration during manufacturing is preferably 1 to 30% by mass, more preferably 5 to 20% by mass, considering the factors that minimize polymer precipitation and facilitate the production of high molecular weight polymers. Furthermore, to prevent hydrolysis of the tetracarboxylate dichloride, the organic solvent used in the manufacture of the polyamic acid ester is preferably dehydrated as much as possible, and the process is preferably carried out in a nitrogen atmosphere to prevent the ingress of outside air.
[0119] (3) Cases involving the manufacture of tetracarboxylic acid diesters and diamines.
[0120] Polyamates can be manufactured by polycondensation of a tetracarboxylic acid diester and a diamine. Specifically, they can be manufactured by reacting a tetracarboxylic acid diester and a diamine in the presence of a condensing agent, a base, and an organic solvent at 0–150°C, preferably 0–100°C, for 30 minutes to 24 hours, preferably 3–15 hours.
[0121] As the aforementioned condensing agent, triphenyl phosphite, dicyclohexylcarbodiimide, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride, N,N'-carbonyldiimidazole, dimethoxy-1,3,5-triazinylmethylmorpholinium, O-(benzotriazol-1-yl)-N,N,N',N'-tetramethylureon tetrafluoroborate, O-(benzotriazol-1-yl)-N,N,N',N'-tetramethylureon hexafluorophosphate, and (2,3-dihydro-2-thio-3-benzoxazolyl)phosphonate diphenyl ester, etc., are preferred. The amount of condensing agent added is preferably 2 to 3 molar amounts relative to the tetracarboxylic acid diester.
[0122] As the aforementioned base, tertiary amines such as pyridine and triethylamine can be used. From the viewpoint of being an amount that is easy to remove and that it is easy to obtain a high molecular weight product, the amount of base added is preferably 2 to 4 times the molar amount relative to the diamine component.
[0123] Furthermore, in the above reaction, the reaction proceeds efficiently by adding a Lewis acid as an additive. Lithium halides such as lithium chloride and lithium bromide are preferred as Lewis acids. The amount of Lewis acid added is preferably 0 to 1.0 molar ratio relative to the diamine content.
[0124] Of the three methods for manufacturing polyamic acid esters described above, the method described in (1) or (2) is particularly preferred in order to obtain polyamic acid esters with high molecular weight.
[0125] The polyamic acid ester solution obtained by the above operation can be injected into a poor solvent while being thoroughly stirred, causing the polymer to precipitate. Multiple precipitation processes can be performed. After washing with the poor solvent, the purified polyamic acid ester powder is obtained by drying at room temperature or by heating. The poor solvent is not particularly limited, but examples include water, methanol, ethanol, hexane, butyl cellosolve, acetone, and toluene.
[0126] <Polyimide>
[0127] The polyimide used in this invention (the imidized polymer in component (A)) can be manufactured by imidizing the aforementioned polyamic acid ester or polyamic acid.
[0128] In the case of manufacturing polyimides from polyamic acid, chemical imidization by adding a catalyst to a solution of the aforementioned polyamic acid obtained through the reaction of a diamine component and a tetracarboxylic dianhydride is relatively simple. This chemical imidization is preferred because it is carried out at a lower temperature and the molecular weight of the polymer is less likely to decrease during the imidization process.
[0129] Chemical imidization can be carried out by stirring the polyamic acid to be imidized in an organic solvent in the presence of a basic catalyst and an acid anhydride. The organic solvent used in the aforementioned polymerization reaction can be used. Examples of basic catalysts include pyridine, triethylamine, trimethylamine, tributylamine, and trioctylamine. Pyridine is preferred due to its moderate basicity for the reaction. Furthermore, examples of acid anhydrides include acetic anhydride, trimellitic anhydride, and pyromellitic anhydride. Acetic anhydride is preferred because it facilitates purification after the reaction.
[0130] The temperature for the above imidization reaction is -20 to 140°C, preferably 0 to 100°C, and the reaction time can be 0.5 to 100 hours, preferably 1 to 80 hours. The amount of alkaline catalyst is 0.5 to 30 molar times that of the amic acid, preferably 2 to 20 molar times, and the amount of acid anhydride is 1 to 50 molar times that of the amic acid, preferably 3 to 30 molar times. The imidization rate of the obtained polymer can be controlled by adjusting the amount of catalyst, temperature, and reaction time.
[0131] Since the added catalyst or the like may remain in the solution after the imidization reaction of polyamic acid or polyamic acid, it is preferable to recover the obtained imidized polymer by means described below, and then dissolve it again with an organic solvent, so as to use it as component (A) of the liquid crystal alignment agent of the present invention.
[0132] The polyimide solution obtained by the above operation can be injected into a poor solvent while being thoroughly stirred, thereby precipitating the polymer. Multiple precipitation processes can be performed. After washing with the poor solvent, the purified polyimide powder is obtained by drying at room temperature or by heating.
[0133] The aforementioned unsuitable solvents are not specifically limited, but can include methanol, acetone, hexane, butyl cellosolve, heptane, methyl ethyl ketone, methyl isobutyl ketone, ethanol, toluene, benzene, etc.
[0134] <Side-chain acrylic polymers>
[0135] The side-chain acrylic polymer, which is one of the components of (A) of the present invention, exhibits liquid crystal properties and photosensitivity within a specified temperature range.
[0136] Side-chain acrylic polymers are preferably reacted with light in the wavelength range of 200–450 nm and exhibit liquid crystal properties in the temperature range of 100–300 °C.
[0137] As a side-chain type acrylic polymer, it is preferable to have a photosensitive side chain that reacts under light in a wavelength range of preferably 200 to 450 nm, more preferably 250 to 400 nm.
[0138] As a side-chain type acrylic polymer, it is preferable to have a liquid crystal proto-group for exhibiting liquid crystal properties in a temperature range of preferably 100 to 350°C, more preferably 120 to 300°C.
[0139] Side-chain acrylic polymers have photosensitive side chains bonded to their main chain, which can undergo cross-linking, isomerization, or photo-Fries rearrangement in response to light. Ideally, the photosensitive side chains should undergo either cross-linking or photo-Fries rearrangement in response to light; more ideally, they should undergo cross-linking. In this case, the achieved orientation control can be maintained stably over a long period even when exposed to external stresses such as heat.
[0140] The structure of a side-chain acrylic polymer film exhibiting liquid crystal properties is not particularly limited as long as it satisfies these characteristics; however, it is preferable to have a liquid crystal precursor component with a rigid side chain structure. In this case, stable liquid crystal alignment can be obtained when the side-chain acrylic polymer is used to make a liquid crystal alignment film.
[0141] As for the structure of side-chain acrylic polymers, the preferred structures are, for example, those having a main chain and side chains bonded thereto, wherein the side chains have liquid crystal precursor components such as biphenyl, terphenyl, phenylcyclohexyl, phenylbenzoate, azophenyl, etc., and photosensitive groups bonded to the front end that undergo cross-linking and isomerization reactions; or having a main chain and side chains bonded thereto, wherein the side chains have phenylbenzoate groups that become liquid crystal precursor components and undergo photoFries rearrangement reactions.
[0142] As a specific example of the structure of a side-chain type acrylic polymer, a preferred structure is one having a main chain of a free radical polymerizable group derived from at least one compound selected from the group consisting of hydrocarbons, (meth)acrylates, itaconic acid esters, fumarates, maleates, α-methylene-γ-butyrolactone, styrene, vinyl groups, maleimide, and norbornene, and a side chain consisting of at least one of the following formulas (i) to (v).
[0143]
[0144] In the formula, Ar1 represents a divalent substituent obtained by removing two hydrogen atoms from a benzene ring, naphthalene ring, pyrrole ring, furan ring, thiophene ring, or pyridine ring.
[0145] Ar2 and Ar3 independently represent divalent substituents obtained by removing two hydrogen atoms from a benzene ring, naphthalene ring, pyrrole ring, furan ring, thiophene ring, or pyridine ring. One of q1 and q2 is 1, and the other is 0.
[0146] Ar4 and Ar5 independently represent divalent substituents obtained by removing two hydrogen atoms from a benzene ring, naphthalene ring, pyrrole ring, furan ring, thiophene ring, or pyridine ring. Y1-Y2 represent -CH=CH-, -CH=N-, -N=CH-, or -C≡C-.
[0147] S1, S2, and S3 independently represent a single bond, a straight-chain or branched alkylene group having 1 to 18 carbon atoms, a cycloalkylene group having 5 to 8 carbon atoms, a phenylene group, or a biphenylene group; or represent one or more bonds selected from single bonds, ether bonds, ester bonds, amide bonds, urea bonds, carbamate bonds, amino bonds, carbonyl groups, or combinations thereof; or represent a structure formed by bonding two or more but less than ten sites selected from straight-chain or branched alkylene groups having 1 to 18 carbon atoms, cycloalkylene groups having 5 to 8 carbon atoms, phenylene groups, biphenylene groups, or combinations thereof via the aforementioned bonds. It should be noted that the aforementioned divalent substituents can be multiple substituents linked together by the aforementioned bonds to form a structure.
[0148] R 11 It represents a hydrogen atom, hydroxyl group, mercapto group, amino group, alkyl group with 1 to 10 carbon atoms, alkoxy group with 1 to 10 carbon atoms, alkylamino group with 1 to 8 carbon atoms, or dialkylamino group with 2 to 16 carbon atoms.
[0149] The aforementioned benzene ring and / or naphthalene ring may be optionally substituted by one or more identical or different groups selected from halogen atoms, cyano, nitro, carboxyl, and alkoxycarbonyl groups having 2 to 11 carbon atoms. In this case, the alkyl group having 1 to 10 carbon atoms may be straight-chain, branched, cyclic, or a combination thereof, and may also be substituted by halogen atoms.
[0150] The side-chain acrylic polymers of the present invention preferably contain liquid crystal side chains.
[0151] The liquid crystal precursor group in the liquid crystal side chain can be a group that is itself a liquid crystal precursor, such as biphenyl or phenylbenzoate, or a group that forms a liquid crystal precursor structure through hydrogen bonding between side chains, such as benzoic acid. The following structure is preferred as the liquid crystal precursor group in the side chain.
[0152]
[0153] <Side-chain acrylic polymers>
[0154] The side-chain acrylic polymers of the present invention can be obtained by polymerizing the above-mentioned photoreactive side-chain monomers having photosensitive side chains and liquid crystal side-chain monomers.
[0155] [Photoreactive side-chain monomers]
[0156] Photoreactive side-chain monomers refer to monomers of polymers that can form photosensitive side chains at the side chain sites of polymers during polymer formation.
[0157] As a photoreactive group in the side chain, the structure represented by the above formulas (i) to (v) is preferred.
[0158] More specific examples of photoreactive side-chain monomers are preferably structures having a radical polymerizable group of at least one compound selected from the group consisting of hydrocarbons, (meth)acrylates, itaconic acid esters, fumarates, maleates, α-methylene-γ-butyrolactone, styrene, vinyl compounds, maleimide, and norbornene, and a photosensitive side chain composed of at least one of the group consisting of formulas (i) to (v) above.
[0159] [Liquid crystal side chain monomer]
[0160] Liquid crystal side chain monomers refer to monomers from which polymers exhibit liquid crystal properties and which can form liquid crystal precursor groups at the side chain sites.
[0161] More specific examples of liquid crystallizable side chain monomers are preferably those comprising: a radical polymerizable group selected from at least one compound chosen from the group consisting of hydrocarbons, (meth)acrylates, itaconic acid esters, fumarates, maleates, α-methylene-γ-butyrolactone, styrene, vinyl compounds, maleimide, and norbornene; and a liquid crystallizable side chain having at least one of the aforementioned liquid crystallizable groups.
[0162] The side-chain acrylic polymers of the present invention can be obtained by polymerization of the above-described photoreactive side-chain monomers exhibiting liquid crystal properties. Alternatively, they can be obtained by copolymerization of photoreactive side-chain monomers that do not exhibit liquid crystal properties and liquid crystal side-chain monomers, or by copolymerization of photoreactive side-chain monomers that exhibit liquid crystal properties and liquid crystal side-chain monomers. Furthermore, they can be copolymerized with other monomers within a range that does not impair the ability to exhibit liquid crystal properties.
[0163] Other monomers include, for example, industrially available monomers that can undergo free radical polymerization.
[0164] Other specific examples of monomers include unsaturated carboxylic acids, acrylates, methacrylates, maleimides, acrylonitrile, maleic anhydride, styrene compounds, vinyl compounds, etc.
[0165] Specific examples of unsaturated carboxylic acids include acrylic acid, methacrylic acid, itaconic acid, maleic acid, and fumaric acid.
[0166] Examples of acrylates include: methyl acrylate, ethyl acrylate, isopropyl acrylate, benzyl acrylate, naphthyl acrylate, anthraquinone acrylate, anthraquinone methyl acrylate, phenyl acrylate, 2,2,2-trifluoroethyl acrylate, tert-butyl acrylate, cyclohexyl acrylate, isobornyl acrylate, 2-methoxyethyl acrylate, methoxytriethylene glycol acrylate, 2-ethoxyethyl acrylate, tetrahydrofurfuryl acrylate, 3-methoxybutyl acrylate, 2-methyl-2-adamantyl acrylate, 2-propyl-2-adamantyl acrylate, 8-methyl-8-tricyclodecyl acrylate, 8-ethyl-8-tricyclodecyl acrylate, etc.
[0167] Examples of methacrylates include: methyl methacrylate, ethyl methacrylate, isopropyl methacrylate, benzyl methacrylate, naphthyl methacrylate, anthracene methacrylate, anthracene methyl methacrylate, phenyl methacrylate, 2,2,2-trifluoroethyl methacrylate, tert-butyl methacrylate, cyclohexyl methacrylate, isobornyl methacrylate, 2-methoxyethyl methacrylate, methoxytriethylene glycol methacrylate, 2-ethoxyethyl methacrylate, tetrahydrofurfuryl methacrylate, 3-methoxybutyl methacrylate, 2-methyl-2-adamantyl methacrylate, 2-propyl-2-adamantyl methacrylate, 8-methyl-8-tricyclodecyl methacrylate, and 8-ethyl-8-tricyclodecyl methacrylate. Alternatively, glycidyl acrylate, (3-methyl-3-oxetyl)methacrylate, (3-ethyl-3-oxetyl)methacrylate, (3-ethyl-3-oxetyl)methacrylate, and other (meth)acrylate compounds with cyclic ether groups can also be used.
[0168] Examples of vinyl compounds include vinyl ethers, methyl vinyl ethers, benzyl vinyl ethers, 2-hydroxyethyl vinyl ethers, phenyl vinyl ethers, propyl vinyl ethers, etc.
[0169] Examples of styrene compounds include styrene, methylstyrene, chlorostyrene, and bromostyrene.
[0170] Examples of maleimide compounds include maleimide, N-methylmaleimide, N-phenylmaleimide, and N-cyclohexylmaleimide.
[0171] The method for manufacturing the side-chain acrylic polymer of the present invention is not particularly limited, and commonly used industrial methods can be employed. Specifically, it can be manufactured by using vinyl monomers with liquid crystal side chains, photoreactive side chains, cationic polymerization, free radical polymerization, anionic polymerization, etc. Among these, free radical polymerization is particularly preferred from the viewpoint of ease of reaction control.
[0172] The polymerization initiators for free radical polymerization can be well-known free radical polymerization initiators such as AIBN (azobisisobutyronitrile), and well-known compounds such as reversible addition-fragmentation chain transfer (RAFT) polymerization reagents.
[0173] There are no particular limitations to free radical polymerization; emulsion polymerization, suspension polymerization, dispersion polymerization, precipitation polymerization, bulk polymerization, solution polymerization, etc., can be used.
[0174] The organic solvent used in the polymerization reaction of the aforementioned side-chain acrylic polymers is not particularly limited as long as it dissolves the resulting polymer. Specific examples are given below.
[0175] Examples include: N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, N-methylcaprolactam, dimethyl sulfoxide, tetramethylurea, pyridine, dimethyl sulfone, hexamethyl sulfoxide, γ-butyrolactone, isopropyl alcohol, methoxymethylpentanol, dipentene, ethylpentyl ketone, methyl nonyl ketone, methyl ethyl ketone, methyl isopentyl ketone, methyl isopropyl ketone, methyl cellosolve, ethyl cellosolve, methyl cellosolve acetate, and ethyl cellosolve. Acetate, Butyl Carbitol, Ethyl Carbitol, Ethyl Glycol, Ethyl Glycol Monoacetate, Ethyl Glycol Monoisopropyl Ether, Ethyl Glycol Monobutyl Ether, Propylene Glycol, Propylene Glycol Monoacetate, Propylene Glycol Monomethyl Ether, Propylene Glycol-tert-butyl Ether, Dipropylene Glycol Monomethyl Ether, Diethylene Glycol Monoacetate, Diethylene Glycol Dimethyl Ether, Dipropylene Glycol Monoacetate Monomethyl Ether, Dipropylene Glycol Monoethyl Ether, Dipropylene Glycol Monopropyl Ether, Dipropylene Glycol Monoacetate Monopropyl ether, 3-methyl-3-methoxybutyl acetate, tripropylene glycol methyl ether, 3-methyl-3-methoxybutanol, diisopropyl ether, ethyl isobutyl ether, diisobutylene, amyl acetate, butyl butyrate, butyl ether, diisobutyl ketone, methylcyclohexene, propyl ether, dihexyl ether, dioxane, tetrahydrofuran, n-hexane, n-pentane, n-octane, diethyl ether, cyclohexanone, ethylene carbonate, propylene carbonate, methyl lactate, ethyl lactate, methyl acetate, n-butyl acetate, Propylene glycol monoethyl ether, methyl pyruvate, ethyl pyruvate, methyl 3-methoxypropionate, methyl 3-ethoxypropionate, ethyl 3-methoxypropionate, 3-ethoxypropionic acid, 3-methoxypropionic acid, propyl 3-methoxypropionate, butyl 3-methoxypropionate, diethylene glycol dimethyl ether, 4-hydroxy-4-methyl-2-pentanone, 3-methoxy-N,N-dimethylpropaneamide, 3-ethoxy-N,N-dimethylpropaneamide, 3-butoxy-N,N-dimethylpropaneamide, etc.
[0176] These organic solvents can be used alone or in combination. Furthermore, even solvents that do not dissolve the generated polymers can be mixed with the aforementioned organic solvents to prevent the generated polymers from precipitating.
[0177] Furthermore, in free radical polymerization, oxygen in the organic solvent becomes a cause of inhibition of the polymerization reaction; therefore, it is preferable to use an organic solvent that is degassed to the extent possible.
[0178] The polymerization temperature during free radical polymerization can be any temperature from 30 to 150°C, preferably in the range of 50 to 100°C.
[0179] Furthermore, the reaction can be carried out at any concentration, but if the concentration is too low, it is difficult to obtain a high molecular weight polymer, and if the concentration is too high, the viscosity of the reaction solution becomes too high, making it difficult to stir evenly. Therefore, the monomer concentration is preferably 1 to 50% by mass, more preferably 5 to 30% by mass. Preferably, the reaction is carried out at a high concentration initially, followed by the addition of an organic solvent.
[0180] In the above-mentioned free radical polymerization reaction, when the ratio of free radical polymerization initiator to monomer is relatively high, the molecular weight of the obtained polymer is smaller; when the ratio of free radical polymerization initiator to monomer is relatively low, the molecular weight of the obtained polymer is larger. Therefore, the ratio of free radical polymerization initiator to monomer is preferably 0.05 to 15 mol%, more preferably 0.1 to 10 mol%. In addition, various monomer components, organic solvents, free radical polymerization initiators, etc., may be added during polymerization.
[0181] When recovering the polymer from the reaction solution containing side-chain acrylic polymers obtained through the above polymerization reaction, it is preferable to precipitate the polymer by adding the reaction solution to a poor solvent. Examples of poor solvents for precipitation include methanol, acetone, hexane, heptane, butyl cellosolve, heptane, methyl ethyl ketone, methyl isobutyl ketone, ethanol, toluene, benzene, diethyl ether, methyl ethyl ether, and water. The polymer precipitated in the poor solvent is preferably recovered by filtration and then dried at room temperature or by heating under normal or reduced pressure. Furthermore, repeating the process of redissolving and reprecipitating the recovered polymer in an organic solvent 2 to 10 times can reduce impurities in the polymer. Examples of poor solvents for reprecipitation include alcohols, ketones, ethers, and hydrocarbons; using three or more of these poor solvents further improves purification efficiency and is therefore preferred.
[0182] For the molecular weight of the side-chain acrylic polymer of the present invention, taking into account the strength of the obtained coating, the workability during coating formation, and the uniformity of the coating, the weight-average molecular weight measured by GPC (Gel Permeation Chromatography) is preferably 2,000 to 500,000, more preferably 5,000 to 100,000.
[0183] The polymer content of component (A) in the liquid crystal alignment agent of the present invention can be appropriately varied according to the desired coating thickness. From the viewpoint of forming a uniform and defect-free coating, it is preferably 1% by weight or more, and from the viewpoint of the storage stability of the solution, it is preferably 10% by weight or less, wherein 3 to 7% by weight is preferred.
[0184] <(B) Component>
[0185] The liquid crystal alignment agent of the present invention contains component (B), which is a compound represented by the following formula (1).
[0186]
[0187] (where Q is in the formula) 1 and Q 2 Q is selected from one of the following formulas (Q1-1) and single bonds. 1 and Q 2 At least one of them is equation (Q1-1). q1 and q2 are independently 0 or 1, respectively. R 2 and R 3 R can be any one of the groups having an epoxy site and a hydrogen atom, respectively. 2 and R 3 At least one of them is a group having an epoxy site.
[0188]
[0189] (In formula (Q1-1), R) 1 It can be a hydrogen atom or a monovalent organic group. R 1 The monovalent organic group is more preferably methyl, phenyl, a group having an epoxy site, or a thermally decomposable leaving group.
[0190] A thermally decomposable leaving group refers to a substituent that is removed by heating and replaced by a hydrogen atom. This thermally decomposable leaving group is a protecting group of an amino group; its structure is not particularly limited as long as it is a functional group that is replaced by a hydrogen atom by heat. From the viewpoint of the storage stability of the liquid crystal alignment agent, this protecting group D preferably does not decompose at room temperature, is more preferably a protecting group that decomposes under heat treatment at 80°C or above, and is even more preferably a protecting group that decomposes under heat treatment at 100°C or above. From the perspective of the decomposition temperature, tert-butoxycarbonyl or 9-fluorenylmethoxycarbonyl is particularly preferred for D.
[0191] As R 1 R 2 and R 3 The groups with epoxy sites in the definition can be listed as glycidyl groups, 3,4-epoxycyclohexyl groups, etc. Glycidyl groups are preferred from the perspective of ease of synthesis.
[0192] Preferred examples of compounds represented by component (B) include, for example, compounds (B-1) to (B-6) listed below.
[0193] (B-1): In the above formula (1), q1 and q2 are 0, Q 1 For (Q1-1), R 2 and R 3 Compounds containing epoxy groups,
[0194] (B-2): In the above formula (1), q1 and q2 are 0, Q 1 For (Q1-1), R 2 For hydrogen atoms, R 3 Compounds containing epoxy groups,
[0195] (B-3): In the above formula (1), q1 and q2 are 1 and Q. 1 For single bond or (Q1-1), Q 2 For (Q1-1), R 2 and R 3 Compounds containing epoxy groups,
[0196] (B-4): In the above formula (1), q1 and q2 are 1 and Q. 1 For single bond or (Q1-1), Q 2 For (Q1-1), R 2 For hydrogen atoms, R 3 It is a compound having an epoxy group.
[0197] (B-5): In the above formula (1), q1 and q2 are 1 and Q. 1 For (Q1-1), Q 2 For single bond, R 2 and R 3 Compounds containing epoxy groups,
[0198] (B-6): In the above formula (1), q1 and q2 are 1 and Q. 1 For (Q1-1), Q 2 For single bond, R 2 For hydrogen atoms, R 3 It is a compound having an epoxy group.
[0199] As a preferred component (B) mentioned above, compounds represented by any of the following formulas B-1-1 to B-5-1 can be listed as examples.
[0200]
[0201] The compound of component (B) can be obtained by cyclization by treating the addition reactant obtained by reacting the diamine represented by the following formula (0) with an epoxy halopropane using a base pair.
[0202]
[0203] As the diamine represented by formula (0), a known diamine can be used.
[0204] In manufacturing formula (1) R 2and R 3 When both are compounds having groups with epoxy sites, an epoxy halide of 4 equivalents or more, preferably 8 equivalents or more, is used relative to the diamine represented by formula (0), and the mixture is then treated with a base. In the manufacture of R... 1 When the compound is a group with an epoxy site, a corresponding amount of epoxy halide can be used. In order to manufacture R... 2 and R 3 When one of the components is a group with an epoxy site and the other is a hydrogen atom, 2 to 2.2 equivalents of epoxy halopropane are used relative to the diamine represented by formula (0), and the mixture is then treated with a base.
[0205] (B) If the content of component (B) is too high, it will affect the alignment of the liquid crystal; if it is too low, the effects of the present invention cannot be fully obtained. Therefore, the content of component (B) in the liquid crystal alignment agent is preferably 0.1 to 20% by mass, more preferably 1 to 10% by mass, relative to component (A) (100% by mass).
[0206] <Liquid Crystal Alignment Agent>
[0207] The liquid crystal alignment agent used in this invention has the form of a solution of at least one polymer (hereinafter referred to as a specific structure polymer) selected from the group consisting of a polyimide precursor (component A) and an imidized polymer of the polyimide precursor, and a compound of component B, dissolved in an organic solvent. The specific structure polymer preferably has a weight-average molecular weight of 2,000 to 500,000, more preferably 5,000 to 300,000, and even more preferably 10,000 to 100,000. Furthermore, the number-average molecular weight is preferably 1,000 to 250,000, more preferably 2,500 to 150,000, and even more preferably 5,000 to 50,000.
[0208] The concentration of the polymer in the liquid crystal alignment agent used in this invention can be appropriately varied according to the desired coating thickness. From the perspective of forming a uniform and defect-free coating, it is preferably 1% by weight or more, and from the perspective of the storage stability of the solution, it is preferably 10% by weight or less.
[0209] The organic solvent (good solvent) contained in the liquid crystal alignment agent used in this invention is not particularly limited as long as it is a solvent that can uniformly dissolve a polymer with a specific structure.
[0210] Examples include: N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, dimethyl sulfoxide, γ-butyrolactone, 1,3-dimethyl-imidazolinone, methyl ethyl ketone, cyclohexanone, cyclopentanone, or 4-hydroxy-4-methyl-2-pentanone, etc.
[0211] Among them, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, and γ-butyrolactone are preferred.
[0212] Furthermore, when the polymer of the present invention has high solubility in a solvent, it is preferable to use the solvents shown in the aforementioned formulas [D-1] to [D-3].
[0213] The good solvent in the liquid crystal alignment agent of the present invention preferably accounts for 20 to 99% by mass of the total solvent contained in the liquid crystal alignment agent. More preferably, it accounts for 20 to 90% by mass, and even more preferably, it accounts for 30 to 80% by mass.
[0214] The liquid crystal alignment agent of the present invention can use a solvent (also known as a poor solvent) that improves the coating properties and surface smoothness of the liquid crystal alignment film when the liquid crystal alignment agent is coated. Specific examples of poor solvents are listed below, but the invention is not limited to these examples.
[0215] Examples include: ethanol, isopropyl alcohol, 1-butanol, 2-butanol, isobutyl alcohol, tert-butyl alcohol, 1-pentanol, 2-pentanol, 3-pentanol, 2-methyl-1-butanol, isopentyl alcohol, tert-pentyl alcohol, 3-methyl-2-butanol, neopentyl alcohol, 1-hexanol, 2-methyl-1-pentanol, 2-methyl-2-pentanol, 2-ethyl-1-butanol, 1-heptanol, 2-heptanol, 3-heptanol, 1-octanol, 2-octanol, 2-ethyl-1-hexanol, cyclohexanol, 1-methylcyclohexanol, 2-methylcyclohexanol, 3-methylcyclohexanol, 1,2-ethanediol, 1,2-propanediol, 1,3-propanediol, 1,2-butanediol, 1,3- Butanediol, 1,4-Butanediol, 2,3-Butanediol, 1,5-Pentanediol, 2-Methyl-2,4-Pentanediol, 2-Ethyl-1,3-Hexanediol, Dipropyl ether, Dibutyl ether, Dihexyl ether, Dioxane, Ethylene glycol dimethyl ether, Ethylene glycol diethyl ether, Ethylene glycol dibutyl ether, 1,2-Butoxyethane, Diethylene glycol dimethyl ether, Diethylene glycol diethyl ether, Diethylene glycol methyl ethyl ether, Diethylene glycol dibutyl ether, 2-Pentanone, 3-Pentanone, 2-Hexanone, 2-Heptanone, 4-Heptanone, 3-Ethoxybutylacetate, 1-Methylpentylacetate, 2-Ethylbutylacetate, 2-Ethylhexylacetate, Ethylene glycol monoacetate Ethylene glycol diacetate, propylene carbonate, ethylene carbonate, 2-(methoxymethoxy)ethanol, ethylene glycol monobutyl ether, ethylene glycol monoisopentyl ether, ethylene glycol monohexyl ether, 2-(hexyloxy)ethanol, furfuryl alcohol, diethylene glycol, propylene glycol, propylene glycol monobutyl ether, 1-(butoxyethoxy)propanol, propylene glycol monomethyl ether acetate, dipropylene glycol, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol dimethyl ether, tripropylene glycol monomethyl ether, ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, ethylene glycol monobutyl ether acetate, ethylene glycol monoacetate, ethylene glycol diacetate, diethylene glycol monoethyl ether acetate, diethylene glycol monobutyl ether Acetate, 2-(2-ethoxyethoxy)ethyl acetate, diethylene glycol acetate, triethylene glycol, triethylene glycol monomethyl ether, triethylene glycol monoethyl ether, methyl lactate, ethyl lactate, methyl acetate, ethyl acetate, n-butyl acetate, propylene glycol monoethyl ether, methyl pyruvate, ethyl pyruvate, methyl 3-methoxypropionate, methyl 3-ethoxypropionate, ethyl 3-methoxypropionate, 3-ethoxypropionic acid, 3-methoxypropionic acid, propyl 3-methoxypropionate, butyl 3-methoxypropionate, methyl lactate, ethyl lactate, n-propyl lactate, n-butyl lactate, isopentyl lactate, or solvents shown in formulas [D-1] to [D-3] above.
[0216] Preferably, 1-hexanol, cyclohexanol, 1,2-ethanediol, 1,2-propanediol, propylene glycol monobutyl ether, ethylene glycol monobutyl ether, or dipropylene glycol dimethyl ether are used.
[0217] These undesirable solvents are preferably 1 to 80% by mass of the total solvent contained in the liquid crystal alignment agent. More preferably, they are 10 to 80% by mass. More preferably, they are 20 to 70% by mass.
[0218] In addition to the substances described above, the liquid crystal alignment agent of the present invention may also include polymers other than those described in the present invention, dielectrics or conductive substances for changing the dielectric constant, conductivity and other electrical properties of the liquid crystal alignment film, silane coupling agents for improving the adhesion between the liquid crystal alignment film and the substrate, crosslinking compounds for improving the hardness and density of the film when the liquid crystal alignment film is made, and imidization accelerators for efficiently performing the heating imidization based on the polyimide precursor during the firing coating process.
[0219] <Liquid Crystal Alignment Film>
[0220] The liquid crystal alignment film of the present invention is obtained by coating the aforementioned liquid crystal alignment agent onto a substrate, drying, and firing. As for the substrate for coating the liquid crystal alignment agent of the present invention, there are no particular limitations as long as it is a highly transparent substrate; glass substrates, silicon nitride substrates, acrylic substrates, polycarbonate substrates, and other plastic substrates can be used. From the viewpoint of process simplification, using a substrate with ITO electrodes for liquid crystal driving is preferred. Furthermore, for reflective liquid crystal display elements, if it is a substrate on only one side, an opaque object such as a silicon wafer can be used, and the electrodes can be made of light-reflecting materials such as aluminum.
[0221] Methods for applying the liquid crystal alignment agent of the present invention include spin coating, printing, and inkjet coating. The drying and firing processes after applying the liquid crystal alignment agent of the present invention can be performed at any temperature and for any time. Typically, to fully remove the contained organic solvents, the coating is dried at 50°C to 120°C for 1 to 10 minutes, and then fired at 150°C to 300°C for 5 to 120 minutes. The thickness of the fired coating is not particularly limited; however, if it is too thin, the reliability of the liquid crystal display element may decrease. Therefore, the thickness is 5 to 300 nm, preferably 10 to 200 nm.
[0222] Methods for aligning the obtained liquid crystal alignment film include rubbing and photoalignment.
[0223] Friction treatment can be performed using existing friction devices. Examples of materials for the friction cloth include cotton, nylon, and rayon. Typical conditions for friction treatment include a rotational speed of 300–2000 rpm, a conveying speed of 5–100 mm / s, and an indentation of 0.1–1.0 mm. Afterward, residues generated during friction are removed using ultrasonic cleaning with pure water or alcohol.
[0224] As a specific example of the photoalignment treatment method, the following method can be listed: irradiating the surface of the aforementioned coating film with radiation deflected in a predetermined direction, and then, depending on the situation, performing a heat treatment at a temperature of 150–250°C to impart liquid crystal alignment capability. As the radiation, ultraviolet light and visible light with wavelengths of 100–800 nm can be used. Ultraviolet light with wavelengths of 100–400 nm is preferred, and ultraviolet light with wavelengths of 200–400 nm is particularly preferred. Furthermore, to improve liquid crystal alignment, the edge of the coating substrate can be heated at 50–250°C while irradiating with radiation. The irradiation dose of the aforementioned radiation is preferably 1–10,000 mJ / cm². 2 The preferred value is 100–5,000 mJ / cm³. 2 The liquid crystal alignment film manufactured in this way can stably align liquid crystal molecules in a specified direction.
[0225] A higher extinction ratio of polarized ultraviolet light results in greater anisotropy, which is therefore preferable. Specifically, the extinction ratio of linearly polarized ultraviolet light is preferably 10:1 or higher, and more preferably 20:1 or higher.
[0226] The membrane irradiated with polarized radiation as described above can then be contacted with a solvent containing at least one of water and organic solvents.
[0227] As a solvent used in contact treatment, there are no particular limitations as long as it dissolves the decomposition products generated by light irradiation. Specific examples include water, methanol, ethanol, 2-propanol, acetone, methyl ethyl ketone, 1-methoxy-2-propanol, 1-methoxy-2-propanol acetate, butyl cellosolve, ethyl lactate, methyl lactate, diacetone alcohol, methyl 3-methoxypropionate, ethyl 3-ethoxypropionate, propyl acetate, butyl acetate, and cyclohexyl acetate. Two or more of these solvents can be used in combination.
[0228] From the perspective of versatility and safety, at least one of the group consisting of free water, 2-propanol, 1-methoxy-2-propanol, and ethyl lactate is preferred. Water, 2-propanol, and mixed solvents of water and 2-propanol are particularly preferred.
[0229] In this invention, the contact treatment between the membrane irradiated with polarized radiation and the solution containing an organic solvent is performed through a process such as immersion treatment or spray treatment, in which the membrane and the liquid are adequately brought into contact. Among these methods, immersion treatment of the membrane in the solution containing the organic solvent is preferred for 10 seconds to 1 hour, more preferably 1 to 30 minutes. The contact treatment can be performed at room temperature or with heating, preferably at 10 to 80°C, more preferably 20 to 50°C. Furthermore, methods such as ultrasonic waves can be used to improve contact as needed.
[0230] After the above contact treatment, in order to remove the organic solvent from the solution used, one or both of washing (rinsing) and drying based on low-boiling-point solvents such as water, methanol, ethanol, 2-propanol, acetone, and methyl ethyl ketone can be performed.
[0231] Furthermore, the membrane that has undergone solvent-based contact treatment as described above can be heated at 150°C or higher for solvent drying and reorientation of molecular chains in the membrane.
[0232] The preferred heating temperature is 150–300°C. Higher temperatures promote molecular chain reorientation, but excessively high temperatures may lead to molecular chain decomposition. Therefore, a heating temperature of 180–250°C is more preferred, and particularly 200–230°C is especially preferred.
[0233] If the heating time is too short, the molecular chain reorientation effect may not be achieved; if it is too long, the molecular chain may decompose. Therefore, 10 seconds to 30 minutes is preferred, and 1 minute to 10 minutes is more preferred.
[0234] Liquid crystal display element
[0235] The liquid crystal display element of the present invention is characterized in that it comprises a liquid crystal alignment film obtained by the aforementioned liquid crystal alignment film manufacturing method.
[0236] The liquid crystal display element of the present invention is manufactured by obtaining a substrate with a liquid crystal alignment film from the liquid crystal alignment agent of the present invention through the aforementioned liquid crystal alignment film manufacturing method, and then fabricating a liquid crystal cell according to a known method, and using it to make a liquid crystal display element.
[0237] As an example of a liquid crystal cell manufacturing method, a passive matrix structure liquid crystal display element will be used for explanation. It should be noted that an active matrix structure liquid crystal display element, in which switching elements such as TFTs (Thin Film Transistors) are provided in each pixel portion constituting the image display, can also be used.
[0238] First, transparent glass substrates are prepared. A common electrode is disposed on one substrate, and a segment electrode is disposed on the other substrate. These electrodes can be, for example, ITO electrodes, and are patterned in a manner that allows the desired image to be displayed. Next, an insulating film is disposed on each substrate to cover the common electrode and the segment electrode. The insulating film can be, for example, a film composed of SiO2-TiO2 formed by a sol-gel method.
[0239] Next, the liquid crystal alignment film of the present invention is formed on each substrate. Then, one substrate is overlapped on another substrate with their alignment film surfaces facing each other, and the periphery is bonded with a sealing material. In order to control the substrate gap, spacers are typically pre-mixed into the sealing material. Furthermore, it is preferable to pre-distribute spacers for controlling the substrate gap in the in-plane portion where no sealing material is provided. An opening for filling liquid crystal from the outside is pre-formed in a portion of the sealing material.
[0240] Next, liquid crystal material is injected into the space surrounded by the two substrates and the sealing material through an opening in the sealing material. Then, the opening is sealed with an adhesive. Injection can be performed using a vacuum injection method or a method utilizing capillary action in the atmosphere. Next, polarizing plates are installed. Specifically, a pair of polarizing plates are attached to the surfaces of the two substrates opposite to the liquid crystal layer. Through the above steps, the liquid crystal display element of the present invention is obtained.
[0241] In this invention, as a sealant, for example, a resin having reactive groups such as epoxy, acryloyl, methacryloyl, hydroxyl, allyl, and acetyl groups, which is cured by ultraviolet irradiation and heating, can be used. Curing resins having both epoxy and (meth)acryloyl groups are particularly preferred.
[0242] In the sealant of the present invention, inorganic fillers can be mixed in to improve adhesion and moisture resistance. There are no particular limitations on the inorganic fillers that can be used, but specific examples include: spherical silica, fused silica, crystalline silica, titanium dioxide, titanium black, silicon carbide, silicon nitride, boron nitride, calcium carbonate, magnesium carbonate, barium sulfate, calcium sulfate, mica, talc, clay, alumina, magnesium oxide, zirconium oxide, aluminum hydroxide, calcium silicate, aluminum silicate, lithium aluminum silicate, zirconium silicate, barium titanate, glass fiber, carbon fiber, molybdenum disulfide, asbestos, etc. Preferred fillers include spherical silica, fused silica, crystalline silica, titanium dioxide, titanium black, silicon nitride, boron nitride, calcium carbonate, barium sulfate, calcium sulfate, mica, talc, clay, alumina, aluminum hydroxide, calcium silicate, and aluminum silicate. Two or more of the aforementioned inorganic fillers can be mixed together.
[0243] Example
[0244] The following examples illustrate the present invention in detail, but the present invention is not limited to these examples. It should be noted that the abbreviations for compounds have the following meanings.
[0245]
[0246]
[0247] NMP: N-methyl-2-pyrrolidone; BCS: Butyl cellosolve.
[0248] THF: Tetrahydrofuran
[0249] AIBN: 2,2'-Azobisisobutyronitrile
[0250] ( 1 (H-NMR measurement)
[0251] Equipment: Varian NMR system 400NB (400MHz) (manufactured by Varian Corporation) and JMTC-500 / 54 / SS (500MHz) (manufactured by JEOL Corporation)
[0252] Determination solvents: CDCl3 (deuterated chloroform), DMSO-d6 (deuterated dimethyl sulfoxide)
[0253] Reference material: TMS (tetramethylsilane) (δ: 0.0 ppm, 1 H) and CDCl3 (δ: 77.0 ppm, 13 C)
[0254] <Synthesis of Additive E1>
[0255]
[0256] Epichlorohydrin (52.1 g) and 4,4'-diamino-N-methyldiphenylamine (10.0 g, 46.9 mmol) were added to toluene (25 g) and purified water (2.5 g), and stirred at 80 °C for 4 hours. After cooling to room temperature, tetrabutylammonium bisulfate (0.48 g) and 48% sodium hydroxide aqueous solution (23.5 g) were added, and stirred at 35 °C for 3 hours, followed by stirring at room temperature for 16 hours. Purified water (50 g) was added, and the mixture was separated. The oil layer was washed with purified water (50 g), and then dehydrated using magnesium sulfate. The filtrate was concentrated to obtain a crude product. The crude product was dissolved in toluene (150 g) and then filtered using a Kiriyama funnel with silica gel (20 g) lined on the filter surface. Then, after passing toluene (50g), all the filtrate was concentrated to obtain compound [E1] (yield: 13.2g, yield: 64%, amber viscous substance).
[0257] 1H-NMR (400MHz, DMSO-d6, δppm): 6.78-6.73 (m, 8H), 3.59 (t, 4H, J = 16Hz), 3 .38-3.26(m,4H),3.13-3.04(m,7H),2.75-2.71(m,4H),2.58-2.55(m,4H).
[0258] <Synthesis of Additive E2>
[0259]
[0260] Epichlorohydrin (55.4 g) and 4,4'-diaminodiphenyl ether (10.0 g, 49.9 mmol) were added to toluene (25 g) and pure water (2.5 g), and the mixture was stirred at 80 °C for 23 hours. After cooling to room temperature, tetrabutylammonium bisulfate (0.51 g) and 48% sodium hydroxide aqueous solution (25.0 g) were added, and the mixture was stirred at 35 °C for 5 hours. Pure water (50 g) was added, and the mixture was separated. After washing the oil layer with pure water (50 g), the oil was dehydrated with magnesium sulfate, and the filtrate was concentrated to obtain a crude product. The crude product was dissolved in toluene (150 g), and then filtered using a Kiriyama funnel with silica gel (20 g) on the filter surface. After passing toluene (50 g) through the filter, all the filtrate was concentrated to obtain compound [E2] (yield: 15.3 g, 72%, orange viscous substance).
[0261] 1H-NMR (400MHz, DMSO-d6, δppm): 6.84-6.80 (m, 8H), 3.64 (t, 4H, J = 16Hz), 3 .40-3.28(m,4H),3.14-3.08(m,4H),2.76-2.72(m,4H),2.59-2.56(m,4H).
[0262] <Viscosity>
[0263] In the synthesis example, the viscosity of the polymer solution was measured using a TVE-22H type E viscometer (manufactured by Toki Sangyo Co., Ltd.) with a sample volume of 1.1 mL, a conical rotor TE-1 (1°34', R24), and a temperature of 25°C.
[0264] (Synthesis example 1)
[0265] 57.3 g (200 mmol) of DA-1 was measured into a 5 L four-necked flask equipped with a stirrer and a nitrogen inlet tube. 1147 g of NMP was added, and the solution was dissolved by stirring while introducing nitrogen. While stirring the diamine solution under water cooling, 29.4 g (150 mmol) of CA-1 and 191 g of NMP were added. The mixture was stirred at 23 °C for 1 hour under a nitrogen atmosphere. Subsequently, 119.3 g (400 mmol) of DA-2 and 60.1 g (400 mmol) of DA-3 were measured, and 1721 g of NMP was added. The solution was dissolved by stirring while introducing nitrogen. While stirring the diamine solution under water cooling, 158.8 g (810 mmol) of CA-1 and 765 g of NMP were added. The mixture was stirred at 23 °C for 6 hours under a nitrogen atmosphere to obtain a polyamic acid solution (viscosity 180 mPa·s).
[0266] (Synthesis example 2)
[0267] MA1 (5.3 g) and MA2 (19.6 g) were dissolved in THF (102.6 g), degassed using a diaphragm pump, and then AIBN (0.39 g) was added for further degassed. The mixture was then reacted at 60 °C for 8 hours to obtain a polymer solution of methacrylate. This polymer solution was added dropwise to methanol (600 ml), and the resulting precipitate was filtered. The precipitate was washed with methanol and dried under reduced pressure in an oven at 40 °C to obtain methacrylate polymer powder MP1.
[0268] [Example 1] and [Comparative Examples 1 and 2]
[0269] For the polyamic acid solution obtained in Synthesis Example 1, solvent and additives were added while stirring so that the composition of the obtained liquid crystal alignment agent was as shown in Table 1, and then stirred at room temperature for 2 hours to obtain the liquid crystal alignment agent.
[0270] [Table 1]
[0271] Example 1 PAA-A1(100) E1(3) NMP(70), BCS(25) Comparative Example 1 PAA-A1(100) - NMP(70), BCS(25) Comparative Example 2 PAA-A1(100) E2(3) NMP(70), BCS(25)
[0272] ※1: Indicates the content (parts by weight) of each polymer relative to 100 parts by weight of all polymers in the liquid crystal alignment agent.
[0273] ※2: Indicates the content (parts by weight) of each additive relative to 100 parts by weight of all polymers in the liquid crystal alignment agent.
[0274] ※3: Indicates the content (parts by weight) of each solvent relative to 100 parts by weight of the liquid crystal alignment agent.
[0275] [Example 2] and [Comparative Examples 3 and 4]
[0276] NMP was added to the methacrylate powder obtained in Synthesis Example 2, and the mixture was stirred for 30 minutes to obtain a methacrylate polymer solution. Solvent and additives were added while stirring, so that the composition of the obtained liquid crystal alignment agent was as shown in Table 2, and the mixture was stirred at room temperature for 2 hours to obtain the liquid crystal alignment agent.
[0277] [Table 2]
[0278] Example 2 MP1(100) E1(3) NMP(70), BCS(20) Comparative Example 3 MP1(100) - NMP(70), BCS(20) Comparative Example 4 MP1(100) E2(3) NMP(70), BCS(20)
[0279] ※1: Indicates the content (parts by weight) of each polymer relative to 100 parts by weight of all polymers in the liquid crystal alignment agent.
[0280] ※2: Indicates the content (parts by weight) of each additive relative to 100 parts by weight of all polymers in the liquid crystal alignment agent.
[0281] ※3: Indicates the content (parts by weight) of each solvent relative to 100 parts by weight of the liquid crystal alignment agent.
[0282] The following describes a method for manufacturing a liquid crystal cell used to evaluate the mitigation characteristics, flicker characteristics, and liquid crystal alignment of accumulated charge.
[0283] A liquid crystal cell with an FFS (Free-Form-Side) liquid crystal display element structure is fabricated. First, a substrate with electrodes is prepared. The substrate is a glass substrate with dimensions of 30 mm (length), 35 mm (width), and a thickness of 0.7 mm. On the substrate, an IZO electrode constituting the counter electrode is formed across its entire surface as the first layer. On the counter electrode of the first layer, a SiN (silicon nitride) film formed by CVD is formed as the second layer. The SiN film of the second layer has a thickness of 500 nm and functions as an interlayer insulating film. On the SiN film of the second layer, a comb-shaped pixel electrode formed by patterning the IZO film is disposed as the third layer, forming two pixels: the first pixel and the second pixel. Each pixel has dimensions of approximately 10 mm (length) and 5 mm (width). At this point, the counter electrode of the first layer and the pixel electrode of the third layer are electrically insulated by the SiN film of the second layer.
[0284] The pixel electrodes of the third layer have a comb-like shape formed by arranging multiple "く"-shaped electrode elements with a curved central portion. Each electrode element has a short-side width of 3 μm, and the spacing between the electrode elements is 6 μm. Since the pixel electrodes forming each pixel are composed of multiple "く"-shaped electrode elements with a curved central portion, the shape of each pixel is not rectangular, but rather similar to the bold "く" shape, also curved in the center, just like the electrode elements. Furthermore, each pixel is divided into an upper region (top) and a lower region (bottom) by its central curved portion.
[0285] Comparing the first and second regions of each pixel, the forming directions of the electrode elements constituting their pixel electrodes are different. Specifically, based on the rubbing direction of the liquid crystal alignment film (described later), in the first region of the pixel, the electrode elements of the pixel electrode are formed at an angle of +10° (clockwise), while in the second region of the pixel, the electrode elements of the pixel electrode are formed at an angle of -10° (clockwise). In other words, the first and second regions of each pixel are configured such that the directions of the rotational movement (in-plane switching) of the liquid crystal within the substrate surface caused by applying a voltage between the pixel electrode and the counter electrode are opposite to each other.
[0286] Next, the liquid crystal alignment agent obtained in the examples and comparative examples was filtered through a filter with a pore size of 1.0 μm and then spin-coated onto the prepared electrode substrate. After drying on a hot plate at 80°C for 2 minutes, it was fired in a hot air circulating oven at 230°C for 20 minutes to obtain a polyimide film with a thickness of 60 nm. The polyimide film was then rubbed with rayon cloth (roller diameter: 120 mm, roller speed: 500 rpm, moving speed: 30 mm / sec, pressing length: 0.3 mm, rubbing direction: tilted at 10° relative to the IZO comb electrode of the third layer), followed by ultrasonic irradiation in pure water for 1 minute for cleaning, and water droplets were removed by air supply. Subsequently, it was dried at 80°C for 15 minutes to obtain a substrate with a liquid crystal alignment film. Furthermore, as the opposing substrate, a glass substrate with ITO electrodes formed on its back side and columnar spacers with a height of 4 μm is also formed with a polyimide film in the same manner as described above. A substrate with a liquid crystal alignment film having undergone alignment treatment is obtained using the same steps as described above. The two substrates with the liquid crystal alignment film are grouped together, and a sealant is printed in the shape of the liquid crystal injection port remaining on the substrate. Another substrate is then bonded together with the liquid crystal alignment film surfaces facing each other and the friction directions being antiparallel. The sealant is then cured to create empty cells with a cell gap of 4 μm. Liquid crystal MLC-3019 (manufactured by MELCCo., Ltd.) is injected into these empty cells using a reduced-pressure injection method, and the injection port is encapsulated to obtain an FFS-type liquid crystal cell. The obtained liquid crystal cell is then heated at 120°C for 1 hour and placed at 23°C for one night for evaluation of liquid crystal alignment.
[0287] <Mitigating properties of stored charge>
[0288] The liquid crystal unit is placed between two polarizing plates arranged orthogonally to the polarizing axis. With the pixel electrode and the opposing electrode short-circuited and at the same potential, an LED backlight is pre-illuminated from below the two polarizing plates. The angle of the liquid crystal unit is adjusted so that the brightness of the LED backlight transmitted light measured on the two polarizing plates is minimized.
[0289] Next, while applying a rectangular wave with a frequency of 30 Hz to the liquid crystal cell, the VT characteristics (voltage-transmittance characteristics) were measured at a temperature of 23°C, and the AC voltage at which the relative transmittance became 23% was calculated. This AC voltage corresponds to the region where the brightness changes significantly with respect to voltage; therefore, it is convenient to evaluate the stored charge by measuring the brightness.
[0290] Next, at a temperature of 23°C, an AC voltage with a relative transmittance of 23% was applied, and a DC voltage of +1.0V was superimposed after a 5-minute rectangular wave with a frequency of 30Hz was applied, driving for 30 minutes. Afterward, the DC voltage was disconnected, and a rectangular wave with a relative transmittance of 23% and a frequency of 30Hz was applied again for 15 minutes.
[0291] The faster the accumulated charge dissipates, the faster the charge accumulates in the liquid crystal cell when a DC voltage is applied. Therefore, the charge dissipation characteristic is evaluated by the time required for the relative transmittance to decrease by more than 2% immediately after the DC voltage is applied. That is, a decrease of more than 2% in relative transmittance within 30 minutes is defined as "good," and a decrease of no more than 2% in relative transmittance after 30 minutes is defined as "poor."
[0292] <Evaluation of Liquid Crystal Orientation>
[0293] Using this liquid crystal cell, an AC voltage of 9VPP at a frequency of 30Hz was applied for 190 hours at a constant temperature of 60°C. Afterward, the pixel electrode and the opposing electrode of the liquid crystal cell were short-circuited, and the cell was left at room temperature for one day in this state.
[0294] After placement, the liquid crystal unit is positioned between two polarizing plates orthogonally aligned with their polarization axes. The backlight is pre-lit without applied voltage, and the liquid crystal unit's orientation angle is adjusted to minimize transmitted light brightness. Then, the rotation angle Δ is calculated to allow the liquid crystal unit to rotate from the darkest angle in the second region of the first pixel to the darkest angle in the first region. The same angle Δ is calculated for the second pixel by comparing the second and first regions. The average angle Δ values of the first and second pixels are then calculated as the liquid crystal unit's angle Δ. An angle Δ value less than 0.2 degrees is defined as "good" and evaluated as "bad," while an angle Δ value greater than 0.2 degrees is defined as "poor."
[0295] <Evaluation of Voltage Retention Rate (VHR)>
[0296] A voltage of 1V was applied to the obtained liquid crystal cell at 60°C for 60μs, and the voltage was measured after 50ms. The degree to which the voltage could be maintained was calculated as the voltage retention rate. It should be noted that the voltage retention rate was measured using a voltage retention rate measuring device VHR-1 manufactured by TOYOC Corporation.
[0297] <Evaluation of optical properties (transparency)>
[0298] Prepare a quartz substrate with dimensions of 40 mm in length, 40 mm in width, and a thickness of 1.0 mm. Next, filter the liquid crystal alignment agent through a 1.0 μm filter and then spin-coat it onto the quartz substrate. Then, dry it on a hot plate at 80°C for 2 minutes and calcine it at 230°C for 20 minutes to obtain a polyimide film with a thickness of 100 nm on each substrate.
[0299] The transparency was evaluated by measuring the transmittance of the substrate obtained by the aforementioned method. Specifically, a UV-3600 (manufactured by Shimadzu Corporation) was used to measure the transmittance at a temperature of 25°C and a scanning wavelength of 300–800 nm. For reference (reference example), an uncoated quartz substrate was used. For evaluation, the average transmittance over a wavelength of 400–800 nm was calculated; higher transmittance indicated better transparency.
[0300] <Evaluation Results>
[0301] Regarding the liquid crystal display elements using the liquid crystal alignment agents of Examples 1-4 and Comparative Examples 1-3, the results of the evaluation of residual image clearing time, the evaluation of liquid crystal alignment stability, and the evaluation of transparency in the above embodiments are shown in Table 3.
[0302] [Table 3]
[0303]
[0304] ※1: Indicates the content (parts by weight) of each polymer relative to 100 parts by weight of all polymers in the liquid crystal alignment agent.
[0305] ※2: Indicates the content (parts by weight) of each additive relative to 100 parts by weight of all polymers in the liquid crystal alignment agent.
[0306] As can be clearly seen from Table 3, the liquid crystal display element using the liquid crystal alignment agent of Example 1 has excellent voltage retention, rapid charge accumulation, and good liquid crystal alignment and transparency.
[0307] Industrial availability
[0308] The liquid crystal alignment agent of the present invention can be widely used in liquid crystal display elements with longitudinal electric field methods such as TN and VA, and especially with transverse electric field methods such as IPS and FFS.
[0309] It should be noted that the entire contents of the specification, claims and abstract of Japanese Patent Application No. 2018-51092, filed on March 19, 2018, are incorporated herein as the disclosure of the specification of this invention and are included in this application.
Claims
1. A liquid crystal alignment agent comprising component (A), component (B), and an organic solvent. (A) Composition: A photosensitive side-chain acrylic polymer that exhibits liquid crystal properties in the temperature range of 100~300℃. (B) Components: Compounds represented by the following formula (1) In equation (Q1-1), R 1 It can be a hydrogen atom or a monovalent organic group. in, The photosensitive side-chain acrylic polymer of component (A) exhibiting liquid crystal properties in the temperature range of 100-300°C has a side-chain structure consisting of at least one of the following formulas (i) to (v). In formulas (i) to (v), Ar1 is a divalent substituent obtained by removing two hydrogen atoms from a benzene ring, naphthalene ring, pyrrole ring, furan ring, thiophene ring, or pyridine ring. Ar2 and Ar3 are independently divalent substituents obtained by removing two hydrogen atoms from a benzene ring, naphthalene ring, pyrrole ring, furan ring, thiophene ring, or pyridine ring, respectively. One of q1 and q2 is 1, and the other is 0. Ar4 and Ar5 are independently divalent substituents obtained by removing two hydrogen atoms from a benzene ring, naphthalene ring, pyrrole ring, furan ring, thiophene ring, or pyridine ring, respectively. Y1 and Y2 are independently -CH=CH- and -CH= N-, -N=CH-, or -C≡C-, S1, S2, and S3 independently represent a single bond, a straight-chain or branched alkylene group with 1 to 18 carbon atoms, a cycloalkylene group with 5 to 8 carbon atoms, a phenylene group, a biphenylene group, or a divalent substituent formed by a combination of 2 to 10 of these groups, or a structure in which multiple divalent substituents are connected by single bonds, ether bonds, ester bonds, amide bonds, urea bonds, carbamate bonds, amino bonds, or carbonyl bonds, R 11 It can be a hydrogen atom, hydroxyl group, mercapto group, amino group, alkyl group with 1 to 10 carbon atoms, alkoxy group with 1 to 10 carbon atoms, alkylamino group with 1 to 8 carbon atoms, or dialkylamino group with 2 to 16 carbon atoms. The compound represented by component (B) is selected from at least one of the following formulas (B-1) to (B-6). (B-1): In the above formula (1), q1 and q2 are 0 and Q 1 For (Q1-1), R 2 and R 3 Compounds containing epoxy groups, (B-2): In the above formula (1), q1 and q2 are 0 and Q 1 For (Q1-1), R 2 For hydrogen atoms, R 3 Compounds containing epoxy groups, (B-3): In the above formula (1), q1 and q2 are 1 and Q. 1 For (Q1-1), Q 2 For (Q1-1), R 2 and R 3 Compounds containing epoxy groups, (B-4): In the above formula (1), q1 and q2 are 1 and Q. 1 For (Q1-1), Q 2 For (Q1-1), R 2 For hydrogen atoms, R 3 Compounds containing epoxy groups, (B-5): In the above formula (1), q1 and q2 are 1 and Q. 1 For (Q1-1), Q 2 For single bond, R 2 and R 3 Compounds containing epoxy groups, (B-6): In the above formula (1), q1 and q2 are 1 and Q. 1 For (Q1-1), Q 2 For single bond, R 2 For hydrogen atoms, R 3 Compounds containing epoxy groups, The organic solvent is N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, dimethyl sulfoxide, γ-butyrolactone, 1,3-dimethyl-imidazolinone, methyl ethyl ketone, cyclohexanone, cyclopentanone, or 4-hydroxy-4-methyl-2-pentanone.
2. The liquid crystal alignment agent according to claim 1, wherein, The compound of component (B) is selected from at least one of the following formulas: Q1-1-1 to Q1-1-4 and Q1-1-6 to Q1-1-7. 。 3. The liquid crystal alignment agent according to claim 1 or 2, wherein, The organic solvent also includes solvents that improve the coatability and surface smoothness of the liquid crystal alignment film.
4. The liquid crystal alignment agent according to claim 1 or 2, wherein, The liquid crystal alignment agent contains 1 to 10% by mass of a polymer comprising component (A).
5. The liquid crystal alignment agent according to claim 4, wherein, The (B) component is present in 0.1 to 20% by mass relative to the (A) component.
6. A liquid crystal alignment film obtained from any one of claims 1 to 5.
7. A liquid crystal display element comprising the liquid crystal alignment film as described in claim 6.
Citation Information
Patent Citations
Material for liquid crystal alignment and liquid crystal displays made by using the same
WO2004021076A1
Liquid crystl orientating agent and liquid crystal display element using it
WO2004053583A1
Liquid crystal aligning agent, liquid crystal alignment film, and liquid crystal display element
WO2013008822A1
Liquid crystal aligning agent and liquid crystal display element
CN101153995A
Liquid crystal alignment agent, liquid crystal alignment film and liquid crystal display element
CN111868620B